The typicality effect in basic needs. - Pölzler, Thomas; Hannikainen, Ivar R. (Synthese, 2022)
According to the so-called Classical Theory, concepts are mentally represented by individually necessary and jointly sufficient application conditions. One of the principal empirical objections against this view stems from evidence that people judge some instances of a concept to be more typical than others. In this paper we present and discuss four empirical studies that investigate the extent to which this ‘typicality effect’ holds for the concept of basic needs. Through multiple operationalizations of typicality, our studies yielded evidence for a strong effect of this kind: (1) Participants tended to recall the same core examples of the concept in a free-listing task. (2) They judged some basic needs to be more typical than others. (3) The items that were judged to be more typical were listed more frequently in the free-listing task. (4) These items were listed earlier on in the free-listing task. (5) Typical basic needs, as well as non needs, were classified faster than atypical basic needs in a reaction time study. These findings suggest that the concept of basic needs may have a non-classical (e.g., exemplar or prototype) structure. If so, the quest for a simple and robust intensional analysis of the concept may be futile.